Formulation and evaluation of diclofenac emulgel using natural permeation enhancers - Chandra Sekhar Naik D; Shaik Noor Mahammed; Mudigedu Samreen; S. Vamsi; P. Hemalatha (Creative Pharma Assent, 2025)
Background: This study aimed to formulate a stable diclofenac emulgel and determine the penetration rate using different natural penetration enhancers. Methodology: Carbopol (934) and Hydroxypropyl methyl cellulose (HPMC) were utilized as gelling agents due to their favorable viscosity characteristics, which render them widely used for regulating the flow properties of topically administered dosage forms. In the research, diclofenac served as the active ingredient, while Carbopol (934) & HPMC (0.5%) acted as gelling forms to form a proper gel base. Emulsion contains Tween-20 (0.05%), PEG (0.6%), liquid paraffin (0.75%), span-20 (0.1%), along with natural penetration enhancers (0.3%) initially prepared gel base & the emulsion with natural penetration enhancers combine conjointly to shape an appropriate diclofenac emulgel. Results and discussion: According to the study, the improved batch exhibits a 95.08% release in 48 hours and remains stable for about three. The optimized batch exhibits 46.6% suppression in the microbiological assay, whereas the marketed treatment only demonstrates 32.3% inhibition. However, the skin irritation test results have no erythema or edema. The rabbits' skin showed no signs of discomfort. According to stability experiments, the synthesized emulgel's antifungal activity, rheological analysis, in vitro drug release, and physical appearance did not alter after three months of storage. Conclusion: Overall, it was recommended that, in contrast to cream, the emulgel formulation come after the drug release for controlled, long-term drug delivery.